Flip the Cloud: Cyber-Physical Signaling Games in the Presence of Advanced Persistent Threats - Pawlick, Jeffrey; Farhang, Sadegh; Zhu, Quanyan (Decision and Game Theory for Security, 2015)
Access to the cloud has the potential to provide scalable and cost effective enhancements of physical devices through the use of advanced computational processes run on apparently limitless cyber infrastructure. On the other hand, cyber-physical systems and cloud-controlled devices are subject to numerous design challenges; among them is that of security. In particular, recent advances in adversary technology pose Advanced Persistent Threats (APTs) which may stealthily and completely compromise a cyber system. In this paper, we design a framework for the security of cloud-based systems that specifies when a device should trust commands from the cloud which may be compromised. This interaction can be considered as a game between three players: a cloud defender/administrator, an attacker, and a device. We use traditional signaling games to model the interaction between the cloud and the device, and we use the recently proposed FlipIt game to model the struggle between the defender and attacker for control of the cloud. Because attacks upon the cloud can occur without knowledge of the defender, we assume that strategies in both games are picked according to prior commitment. This framework requires a new equilibrium concept, which we call Gestalt Equilibrium, a fixed-point that expresses the interdependence of the signaling and FlipIt games. We present the solution to this fixed-point problem under certain parameter cases, and illustrate an example application of cloud control of an unmanned vehicle. Our results contribute to the growing understanding of cloud-controlled systems.